PENGATURAN REKONSTRUKSI TINDAK PIDANA DALAM UPAYA PEMBUKTIAN DALAM SISTEM PERADILAN PIDANA INDONESIA - Lumbanraja, Sahala J; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Reconstruction is an examination technique in the framework of the investigation, by re-modeling the suspect's manner of committing a crime and / or knowledge of a witness, in order to obtain a clear picture of the occurrence of the offense and to test the truth of the suspect or witness so as to obtain a description of whether or not The suspect as a perpetrator of daan daituangkan in Minutes of Reconstruction. Based on this understanding, the authors formulate two problems, namely: First, how the arrangement of the reconstruction of criminal acts in an attempt to prove in the Indonesian penal system perasilan. Second, what is the urgency of a criminal reconstruction? This type of research can be classified in the research of normative law (legal research) or also called research literature by examining secondary law material or research based on standard rules that have been recorded also called library research, data type used is using secondary data consisting Of primary, secondary and tertiary legal materials. While the data collection used in this writing is the method of literature review or documentary study, the data that has been collected then processed by way of selection, clarified systematically, logically and juridically qualitatively. The author draws a deductive conclusion, drawing the conclusions of the general things to the things that are special. From the research results there are several problems that can be summarized as follows: First, provide an overview of how the arrangement of reconstruction of criminal acts in the Indonesian criminal justice system. Second, give what urgency the reconstruction of a crime is done. Third, as a contribution of thoughts and tools to encourage students to conduct research on the arrangement of the reconstruction of criminal acts in an effort to prove the Indonesian criminal justice system. Keywords: Arrangement – Reconstruction – Verification - Indonesian Justice System - Crime